Effects of acute endurance exercise and exhaustive exercise on innate immune signals induced by mtDNA. (12th October 2022) - Ge, Zhe; Zhang, Zhe; Ding, Shuzhe
Objective: Numerous studies have shown that mitochondrial DNA (mtDNA) can trigger innate immune signaling, and exercise can induce mitochondrial stress. Therefore, this study is aimed at investigating the influence of different types of acute exercise on the innate immune signaling triggered by mtDNA. Methods: Male C57BL/6 mice ( n = 18) were randomly and equally divided into three groups. They were control group, acute moderate-intensity endurance exercise group (AMIE), and 3-day exhaustive exercise group (EE) respectively. Mice were sacrificed immediately after exercise. The spleen, liver, and blood were taken for analysis. Results: The amount of mtDNA in the liver cytoplasm and plasma was significantly decreased after AMIE ( p < .05). However, the amount of mtDNA in plasma was increased after EE (p < .05). The mRNA expression of TFAM, and most TLR9 and cGAS/STING signaling pathway-related genes in the liver and spleen was markedly elevated, whereas the expression of those genes in leukocytes was reduced after AMIE. Furthermore, AMIE significantly decreased the protein expression of NLRP3 inflammasome in the liver ( p < .05) and STING in spleen ( p < .01). Also, AMIE and EE caused a drop in circulating IFN-β levels ( p < .05). Conclusion: A single bout of moderate-intensity exercise reduces mtDNA-induced innate immune signaling and suppresses inflammatory responses by decreasing hepatic cytoplasmic and circulating mtDNA. However, repeated bouts of exhaustive exercise stimulate innate immune signaling by increasing levels of circulating mtDNA.